Social responsibility of firms and the impact of bio-economy in intelligent use of renewable energy sources - Mihai Andronie; Violeta-Elena Simion; Elena Gurgu; Adrian Dijmărescu; Irina Dijmărescu (Amfiteatru Economic Journal, 2019)
Through its whole set of activities related to the invention, development, production and use of biological products and processes, bio-economy contributes significantly to the economy and to the progress of society by improving the sustainability of health, nutrition, energy efficiency, industry, environmental protection and human well-being in general. In this study, by creating an overview of the efficiency of renewable energy sources, in the context of sustainable resource management for preserving a healthy, diverse and resilient ecosystem, the research aimed to show the unused renewable energy sources at maximum potential in Romania, what are the reasons for their non-use, what are the opportunities and what are the solutions that can be adopted for the exploitation of these types of renewable energy sources in Romania. In the European Union, geothermal energy has already been well exploited and, in the future, will no longer make a significant contribution to increasing the productivity of renewable energies. Eurostat data was collected and processed using a linear regression model on the primary production of renewable energy in Romania and the rest of the European states for a period of 11 years (2005-2016); at the same time, statistical forecasts were made for the years 2017 and 2018 and was pursued to what extent social responsibility activities of companies is in line with the principles of bio-economy. In Romania, there is a very high potential for both geothermal energy that is insufficiently exploited to date and for the transformation of municipal waste into energy. It also explores the possibility of using intelligent information systems to optimize the exploitation of renewable energy sources. An important role in this effort is made by companies that, by adopting a Social Responsibility Code (CRS), can bring not only benefits, but also create a positive image with favorable consequences for all parties involved.
Keywords: C2; D66; M30; O3; Q56; 330; social responsibility; bio-economy; natural resources; sustainability; intelligent use of resources